Tetum Acronyms Used on WhatsApp Messages in Timor Leste Communication Context - Antonio Constantino Soares; Muhammad Musawir (Gurindam: Jurnal Bahasa dan Sastra, 2025)
This research aims to investigate the use of Tetum acronyms in WhatsApp messages among the Timorese in Timor-Leste. The topic was chosen due to the increasing prevalence of Tetum acronyms among Tetum speakers in Dili. A qualitative descriptive research method was employed, supported by a documentation technique to collect the data. Once the data were collected, they were analyzed qualitatively. The findings revealed 16 distinct lexical categories in Tetum acronyms. The data included 4 adverbs, 1 verb, 2 adjectives, 5 nouns, 2 pronouns, and 2 grammatical functions.